3D printing of continuous carbon fibre reinforced polymer composites with optimised structural topology and fibre orientation. (1st June 2023) - Zhang, Haoqi; Wang, Shuai; Zhang, Ka; Wu, Jiang; Li, Aonan; Liu, Jie; Yang, Dongmin
Highlights: Sequentially coupled optimisation of structural topology and fibre orientation. Three-point bending test of MBB beam was conducted. Stiffness and strength of the optimal design were increased by 256% and 305% Paths-based modelling illustrated loading was redistributed along optimised fibre paths. Superior lightweight performance was achieved compared to traditional composites. Abstract: This study presents a sequentially coupled optimisation of structural topology and fibre orientation for 3D printing of continuous carbon fibre reinforced polymer composites. Topology optimisation was first performed to obtain the geometry of the structure under a specific load, and then continuous fibres were placed along the identified principal stress trajectories. Composite preforms were 3D printed by a material extrusion-based technique followed by post-processing with vacuum bagging using epoxy for infusion. The case of Messerschmitt-Bolkow-Blohm (MBB) beam under three-point bending test was studied and a path-based model was also built to analyse the effect of customised fibre placement and their lightweight performance. Experimental results showed that 3D printed composites with optimised fibre orientation achieved 305% and 256% higher strength and stiffness than Markforged® printed composites. By comparing with the traditionally-manufactured composites and aerospace-grade aluminium alloy, this study demonstrated the potential of manufacturing ultra-lightweight composite structures via 3D printing and the benefits of fibre orientation optimisation in lightweight design of composites with topology optimisation.